The Effectiveness of Split Dictation as a Teching Strategy to Improve Students' Listening Skill - Kurniawan, Tri Widi; Wahyanti, C Murni (ELT Forum: Journal of English Language Teaching, 2019)
The objectives of this study are to find out whether split dictation technique is an effective technique to improve students’ listening skill and whether there is a significant difference between students who were taught by using split dictation and those who were taught by using a conventional method. This study is a quantitative research using quasy experimental as the method of collecting data. The subject of this research was 72 students of the tenth-grade students of SMA N 1 Sukorejo. In obtaining the data, the researcher conducted the pre-test, treatments, and the post-test. The results of this research showed that the mean score of the experimental group is 82,7 and the control group is 77,638. By using IBM SPSS 23th version program, the computation of the t-test which score of the sig (2 tailed) is (0.000) lower than (0.05), and the result of t-value (4.189) is higher than the t-table (1.994). In conclusion, there is a significant difference between the students’ listening test achievement. The students who were taught by using split dictation has higher achievement, this indicated that split dictation is effective enough to improve students’ listening achievement. Keywords: Split Dictation Technique; Listening Skill